2019
DOI: 10.1002/syn.22127
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in NMDAR‐related amino acids in first episode psychosis

Abstract: The aim of the present study was to explore the role of N‐methyl‐D‐aspartate receptor (NMDAR) related amino acids in drug‐naive first episode psychosis (FEP) patients. The medication naïve patients with FEP (n = 40) and healthy volunteers with no family history of schizophrenia (n = 35) were recruited to the study and followed up for 10 weeks. Liquid chromatography–mass spectrometry method was used to measure plasma levels of the amino acids. The plasma glutamine, glutamic acid, proline, serine, asparagine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Moreover, GLY and SER have been investigated as possible clinical markers for schizophrenia, with some studies demonstrating increased GLY and SER plasma levels in patients after antipsychotic treatment 23 , 65 ; no differences in patients medicated with different antipsychotics 3 , or lower GLY and SER plasma levels in patients in comparison to controls 66 , 67 . A recent study demonstrated high plasma GLN levels in drug-naïve FEP patients, which was negatively correlated with negative symptoms; however no differences in plasma GLN levels were found after treating these patients 68 .…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, GLY and SER have been investigated as possible clinical markers for schizophrenia, with some studies demonstrating increased GLY and SER plasma levels in patients after antipsychotic treatment 23 , 65 ; no differences in patients medicated with different antipsychotics 3 , or lower GLY and SER plasma levels in patients in comparison to controls 66 , 67 . A recent study demonstrated high plasma GLN levels in drug-naïve FEP patients, which was negatively correlated with negative symptoms; however no differences in plasma GLN levels were found after treating these patients 68 .…”
Section: Discussionmentioning
confidence: 92%
“…However, some discrepancy exists between studies. Cai et al (2012) 25 did not find altered Pro level in AP-naïve patients with FEP compared to CSs, however, Garip and Kayir (2019) 26 demonstrated that drug-naïve FEP patients had hyperprolinemia. Pro fulfils several of the classic criteria used to define neurotransmitters 27 and previous results indicate that L-Pro is a weak agonist of the Gly receptor and at both NMDA and non-NMDA Glu receptors 28 .…”
Section: Discussionmentioning
confidence: 95%
“…Boxplots of the statistically significant variation of the errors (residuals) of log-transformed biomarker ratios (derived by regressing out covariate effects) for control subjects and first episode (FEP) patients at baseline (before treatment with antipsychotics (AP)), after 0.6-year, and after 5.1-year treatment with AP. www.nature.com/scientificreports/ FEP compared to CSs, however, Garip and Kayir (2019) 26 demonstrated that drug-naïve FEP patients had hyperprolinemia. Pro fulfils several of the classic criteria used to define neurotransmitters 27 and previous results indicate that L-Pro is a weak agonist of the Gly receptor and at both NMDA and non-NMDA Glu receptors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, myxalamid A was reported to be up-regulated in FEP patients at baseline but down-regulated in follow-up compared with HC. 4-hydroxyproline, as an NMDAR-related amino acid was reported to be elevated in FEP patients and inferred to induce a compensatory response to glutamatergic hypofunction [ 42 ]. Our pathway analysis also identified a potential involvement of the 4-hydroxyproline pathway, which is associated with executive dysfunction in schizophrenia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%